Human genetic information [ science, law, and ethics (Ciba Foundation symposium, 1990)
As part of a continuing effort to tackle issues of major social concern, this 280th conference of internationally recognized experts from the fields of molecular biology, medicine, philosophy, theology, and the law looks into the scientific, legal, ethical, social, and economic issues confronting man and his ability to map and sequence the human genome. A wide variety of subjects are covered, including prenatal diagnosis, advances in the genetics of psychiatric disorders, the problems associated with polygenic disease, and the limits to genetic intervention in humans. The symposium also discus